Energy-efficient medium access control for energy harvesting communications - Fafoutis, Xenofon; Di Mauro, Alessio; Orfanidis, Charalampos; Dragoni, Nicola (IEEE transactions on consumer electronics, 2015)
While energy consumption is widely considered the primary challenge of wireless networked devices, energy harvesting emerges as a promising way of powering the Internet of Things (IoT). In the Medium Access Control (MAC) layer of the communication stack, energy harvesting introduces spatial and temporal uncertainty in the availability of energy. In this context, this paper focuses on the design and implementation of the MAC layer of wireless embedded systems that are powered by energy harvesting; providing novel protocol features and practical experiences to designers of consumer electronics who opt for tailoring their own protocol solutions instead of using the standards.